(untitled) (Research, Society and Development, 2021)
The objective of this study is to describe and analyze the influence of vaccination coverage on the control of immunopreventable diseases in Brazil in national and international publications. This is an integrative review with a qualitative approach. The search strategy was conducted in May 2021, by online access in the databases MEDLINE (Medical Literature Analysis and Retrieval System Online), LILACS (Latin American and Caribbean Literature on Health Sciences), BDENF-Nursing (bibliographic database specialized in the Nursing area) and Coleciona SUS (National Collection of Information Sources of the Unified Health System). The following descriptors were used: vaccination coverage, diseases, and immunization. From the data collection, 633 studies were identified. The first stage of the analysis consisted of applying the inclusion and exclusion criteria. Included in the search were: full articles freely available, Portuguese, English, and Spanish languages. Duplicate articles, theses and dissertations were excluded. Thus, 31 articles were obtained at the end of the first stage. In the second stage, the 31 studies were read to detect those that answered the research’s guiding question. We reached a sample of 8 studies to be analyzed. This study shows that health education actions are needed in Brazil to improve the knowledge, updating and qualification of all professionals, health workers and educators, in order to standardize the information about the vaccination schedule and immunopreventable diseases, thus ruling out possible factors that prevent people from getting vaccinated.